2016
DOI: 10.1089/cap.2015.0192
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response in Pediatric Anxiety Disorders: Implications for Clinical Trial Design and Interpretation

Abstract: Objectives: The characterization and prediction of placebo response in clinical trials of youth with anxiety disorders have received little attention, despite the critical effects of placebo response rate on the success or failure of clinical trials. With this in mind, we sought to examine the factors that predict or influence placebo response in randomized controlled trials of youth with anxiety disorders. Methods: Prospective, randomized, parallel-group controlled trials of psychopharmacologic interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 43 publications
(57 reference statements)
2
30
1
Order By: Relevance
“…Second, just as placebo response has received considerable attention in pediatric mood and anxiety disorders, the impact of placebo-related AEs, which affects our ability to quantify medication-related AEs, may vary as a result of patient expectation, clinician-specific factors (eg, experience with the disorder under study, expertise in the clinical trial population) 62 or trial design (eg, capture of AEs). In this regard, by choosing to examine OCD and anxiety disorders (rather than major depressive disorder), we have selected conditions with lower placebo response rates, [62][63][64] which may minimize the influence of high placebo response on AE reporting. Third, although OCD and anxiety disorders were examined independently with the BHM, we also examined AEs in combined OCD and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Second, just as placebo response has received considerable attention in pediatric mood and anxiety disorders, the impact of placebo-related AEs, which affects our ability to quantify medication-related AEs, may vary as a result of patient expectation, clinician-specific factors (eg, experience with the disorder under study, expertise in the clinical trial population) 62 or trial design (eg, capture of AEs). In this regard, by choosing to examine OCD and anxiety disorders (rather than major depressive disorder), we have selected conditions with lower placebo response rates, [62][63][64] which may minimize the influence of high placebo response on AE reporting. Third, although OCD and anxiety disorders were examined independently with the BHM, we also examined AEs in combined OCD and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common outcome measurements in pediatric psychiatric research is caregiver report. Yet, recent research has illustrated that placebo response rates are approximately 22% and can range up to 50% in children with ASD [King et al, 2013], with similar rates in childhood depression and anxiety [Bridge, Birmaher, Iyengar, Barbe, & Brent, 2009;Dobson & Strawn, 2016], thus, presenting a significant challenge for treatment research. Nevertheless, continued rigorous research is essential in the search for psychopharmacological and behavioral treatments.…”
Section: Introductionmentioning
confidence: 99%
“…First, because of the small sample size, this study is underpowered to detect differences in efficacy between groups. Second, the unbalanced randomization may have further attenuated the ability to detect differences between treatment groups and may have inflated the placebo response rate (e.g., due to increased subject or physician expectation of randomization to active drug/treatment efficacy) (Dobson and Strawn 2016). In this regard, recent studies have shown that treatment expectation at baseline predicts placebo response in clinical trials involving antidepressants in adults (Rutherford et al 2016) and youth (Strawn et al 2016).…”
Section: Discussionmentioning
confidence: 99%